2021
DOI: 10.3390/universe7050139
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Properties of Galaxy Groups

Abstract: Galaxy groups and poor clusters are more common than rich clusters, and host the largest fraction of matter content in the Universe. Hence, their studies are key to understand the gravitational and thermal evolution of the bulk of the cosmic matter. Moreover, because of their shallower gravitational potential, galaxy groups are systems where non-gravitational processes (e.g., cooling, AGN feedback, star formation) are expected to have a higher impact on the distribution of baryons, and on the general physical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 247 publications
(470 reference statements)
2
50
0
Order By: Relevance
“…X relation observed for groups (Helsdon & Ponman, 2000) relative to clusters (White et al, 1997) indicated a significant deviation from the L X ∝ T 2 X relationship expected for virialized gaseous halos retaining all their baryons in hydrostatic equilibrium (e.g., Balogh et al (1999), see companion review by Lovisari et al (2021)).…”
Section: The Baryonic Content Of Group Halosmentioning
confidence: 82%
See 2 more Smart Citations
“…X relation observed for groups (Helsdon & Ponman, 2000) relative to clusters (White et al, 1997) indicated a significant deviation from the L X ∝ T 2 X relationship expected for virialized gaseous halos retaining all their baryons in hydrostatic equilibrium (e.g., Balogh et al (1999), see companion review by Lovisari et al (2021)).…”
Section: The Baryonic Content Of Group Halosmentioning
confidence: 82%
“…The IGrM is mainly very hot (T ∼ 10 7 K), but does not primarily radiate via Bremsstrahlung radiation like the intracluster medium (ICM; see Figure 1 of the companion review by Lovisari et al (2021)). Cooling via line emission offers a greater opportunity to form multi-phase, cool (T < 10 5 K) gas, and potentially provide additional fuel to galaxies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that both types of objects are found in the same, tight, correlation. We won't enter in a detailed discussion of purely X-ray relations and their meaning, we refer the reader to the companion review by Lovisari et al (2021) for a description of X-ray scaling relations in galaxy groups. The result presented in the left panel of Fig.…”
Section: Global Scaling Relationsmentioning
confidence: 99%
“…They are an important laboratory to study how different baryonic processes shape the properties of galaxies that reside in these galaxy groups (McCarthy et al 2010;Le Brun et al 2014;Gu et al 2020). Scaling relations between the observable properties of galaxy groups such as their total group luminosity or group velocity dispersion with the halo mass are crucial to develop a phenomenological understanding of galaxy formation within groups (see e.g., Yang et al 2003;Eke et al 2004b;Yang et al 2007;Sheldon et al 2009;Eckmiller et al 2011;Han et al 2015;Viola et al 2015;Lovisari et al 2020Lovisari et al , 2021Gonzalez et al 2021;Yang et al 2021).…”
Section: Introductionmentioning
confidence: 99%